Resuscitating the Trust of a Chose in Action - THAM, Chee Ho (Institutional Knowledge at Singapore Management University, 2005)
Tham discusses the deeper question of the constitutive intention, where a trust has purportedly been constituted over a contractual promise, needs to be proved on the part of the promisor, the promisee, or both. The need to approach the question of constitutive intention through a wider angled lens has been obscured because of an overly single-minded focus on the purported settlor of the trust.